HAMBATAN PENERAPAN SANKSI PAJAK DI KPP PRATAMA PAMEKASAN - Muhammad Ainul Yaqin; Alwiyah Alwiyah (Universitas Muhammadiyah Malang, 2020)
This research aims to illustrate how the processes/procedures and obstacles in the implementation of tax sanctions in KPP Pratama Pamekasan. The research method used is a case study approach. One key informant with two supporting informants, then the information was analyzed using the Miles and Huberman model consisting of data reduction, data presentation, conclusion drawing, and verification. The result of this research was first, the application of tax sanctions in KPP Pratama Pamekasan only applied to the taxpayer who is active status. Secondly, the socialization of tax sanctions conducted by KPP Pratama Pamekasan through the delivery of chain messages and also through social media has not been conveyed properly to the taxpayers. Thirdly, the barriers experienced by KPP Pratama Pamekasan in applying tax sanctions are the ignorance of taxpayers on the application of the tax sanctions themselves.